New record and natural history notes of the Colombian endemic brown hairy dwarf porcupine, Coendou vestitus - Cortés-Suárez, Javier Ernesto (Therya Notes, 2020)
The brown hairy dwarf porcupine Coendou vestitus is an endemic species to Colombia. Is one of the least studied mammals at the national level, is only known from a small area in the Eastern Cordillera, and is considered data deficient globally by the International Union for Conservation of Nature (IUCN) and threatened at the national level (Vulnerable, VU). During a bird inventory three records of C. vestitus, were occasionally found on the branch of a gaque and roble tree in a fragment of a secondary growth forest in the municipality of Santa Sofia, Department of Boyacá, Colombia. The new records for the species represent the seventh locality from where it is known to occur, and contribute to a better understanding of its distribution and natural history, information that ultimately is indispensable for further conservation actions.